The development of skill and interest in sport - Turnnidge, J.; Allan, V.; Côté, J. (Skill acquisition in sport: research, theory and practice, 2020)
A key question in the sp orts sciences is how to best facilitate skill acquisition in athletes. Accordingly, researchers have focused on examining athlete progression in sport and the long-term outcomes associated with different learning opportunities throughout development. In this chapter, the concepts of early specialization, early sampling, and early engagement, as well their associated developmental pathways are explored. Evidence relating to various types of learning opportunities and motivational processes at different stages of development are reviewed. Finally, practical implications and directions for future research are discussed.